2021
DOI: 10.15766/mep_2374-8265.11090
|View full text |Cite
|
Sign up to set email alerts
|

Quality Improvement Amid a Global Pandemic: A Virtual Curriculum for Medical Students in the Time of COVID-19

Abstract: Introduction The COVID-19 pandemic in March of 2020 necessitated the removal of medical students from direct patient care activities to prevent disease spread and to conserve personal protective equipment. In order for medical student education to continue, virtual and online electives were designed and implemented expeditiously. We created a virtual curriculum that taught quality improvement (QI) skills within the context of the global pandemic. Methods This 4-week cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
13
0
1
Order By: Relevance
“…Likewise, in the present study, gender was not considered an influential factor in the level of knowledge about pharmacological management in pregnant women. This could be due to the fact that, at the time of the questionnaire, the students were in a virtual learning environment, which in some cases has been shown to improve student learning, regardless of gender, facilitating the acquisition of knowledge and decision-making [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, in the present study, gender was not considered an influential factor in the level of knowledge about pharmacological management in pregnant women. This could be due to the fact that, at the time of the questionnaire, the students were in a virtual learning environment, which in some cases has been shown to improve student learning, regardless of gender, facilitating the acquisition of knowledge and decision-making [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These innovations included virtual rounds, virtual radiology experiences, and virtual electives. [8][9][10][11][12] These studies found favorable teaching quality, clinical relevance, and educational value. [8][9][10][11][12] Advantages of remote learning included elimination of commute time, flexibility, the opportunity to pace one's own learning, comfort, and cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12] These studies found favorable teaching quality, clinical relevance, and educational value. [8][9][10][11][12] Advantages of remote learning included elimination of commute time, flexibility, the opportunity to pace one's own learning, comfort, and cost savings. 2 Barriers to remote learning included distractions, Internet problems, anxiety, lack of space, and reduced contact with colleagues.…”
Section: Discussionmentioning
confidence: 99%
“… 14 17 In one study that evaluated a COVID-19 era online quality improvement (QI) curriculum for medical students at the University of Maryland School of Medicine, students demonstrated improvement in QI knowledge, and all students reported that the virtual learning experience was an effective way to deliver QI content and that they were more likely to engage in QI work because of the online course. 18 …”
Section: Discussionmentioning
confidence: 99%